Promoting dual careers at higher education institutions: 31 benefits ranked by the project Student Athletes Erasmus+ Mobility in Europe (SAMEurope) - Hernando Domingo, Carlos; Renau Michavila, Marta; Thorén, Per; Bankel, Johan; Karlsteen, Magnus; Kalaja, Sami; Rasinaho, Minna; Karjalainen, Aki; Scharenberg, Swantje; Kohler, Pascale; Agneray, Florian; Deflon, Alexia; et al. (Frontiers in Sports and Active Living, 2024)
The project Student Athletes Erasmus+ Mobility in Europe identified and defined a total of 31 benefits offered to dual-career student athletes who are combining their university studies with high-level training. The project was co-funded by the European Union and carried out by five universities: Chalmers University of Technology (Sweden), Institut national des sciences appliquées de Lyon (France), University of Jyväskylä (Finland), Karlsruhe Institute of Technology (Germany), and Universitat Jaume I (Spain). The purpose of the study was to rank these benefits by combining the perspectives of the university staff and the student athletes from each university in the consortium. The university staff included experts from sports services and the international relations office. A questionnaire was also sent to the dual-career athletes enrolled at the consortium’s universities. Of the 514 dual-career athletes, 208 (116 women) completed the questionnaire. The overall response rate was 40.47%. The university staff assessed the importance of each benefit, how easy it was to implement at the institution, and whether or not the university offered the benefit to its students. The dual-career students rated each of the 31 benefits and indicated whether or not they had used them. A specific methodology was designed to rank these benefits using the ratings of the university staff and the student athletes. Intra-group and inter-group Pearson correlations were performed. The results show a strong and significant correlation between the benefits from the perspective of the university staff (r=0.710, p=7.76E-7) and from the perspective of the students (r=0.715, p=2.44E-6). The correlation is moderate and significant when the benefits are correlated from the perspective of the two groups as a whole (0.363, p=0.045), with the three most important benefits being the free use of sports facilities, justification for absences, and the adaptation of the pace of studies. The study makes visible the commitment of higher education institutions to facilitating the dual career of student athletes and identifies those benefits that may be of greater interest to European universities as a whole. The European perspective has been considered, while respecting the specificities of each university and the country in which it is located.